Bankruptcy Prediction Analysis Using the Altman Z-Score Method for Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2020-2022 Period - Andira, Ica Puspi; Suprayitno, Eddi; Lubis, Farida Khairani (EDUCTUM: Journal Research, 2025)
This study aims to evaluate the likelihood of bankruptcy in companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period using the Altman Z-Score method. This study applies a quantitative approach and descriptive research. The sample used consisted of 16 companies in the food and beverage subsector selected through purposive sampling techniques based on certain criteria. The analysis results show that most companies have been in the safe zone category for three consecutive years, indicating they have good financial condition and are not at risk of bankruptcy in the near future. Only a small number of companies that were in the gray zone have successfully shown improvement and returned to the safe category. Not a single company was classified as having difficulty. These findings demonstrate the resilience of the food and beverage sector in the face of economic pressures, including during the COVID-19 pandemic.